Summer surface air temperature proxies point to near-sea-ice-free conditions in the Arctic at 127 ka - L. C. Sime; R. Sivankutty; I. Vallet-Malmierca; A. M. de Boer; M. Sicard (Climate of the Past, 2023)
The Last Interglacial (LIG) period, which had higher summer solar insolation than today, has been suggested as the last time that Arctic summers were ice free. However, the latest suite of Coupled Modelling Intercomparison Project 6 Paleoclimate (CMIP6-PMIP4) simulations of the LIG produce a wide range of Arctic summer minimum sea ice area (SIA) results, with a 30 % to 96 % reduction from the pre-industrial (PI) period. Sea ice proxies are also currently neither abundant nor consistent enough to determine the most realistic state. Here we estimate LIG minimum SIA indirectly through the use of 21 proxy records for LIG summer surface air temperature (SSAT) and 11 CMIP6-PMIP4 models for the LIG. We use two approaches. First, we use two tests to determine how skilful models are at simulating reconstructed Δ SSAT from proxy records (where Δ refers to LIG-PI). This identifies a positive correlation between model skill and the magnitude of Δ SIA: the most reliable models simulate a larger sea ice reduction. Averaging the two most skilful models yields an average SIA of 1.3×10 6 km 2 for the LIG. This equates to a 4.5×10 6 km 2 or 79 % SIA reduction from the PI to the LIG. Second, across the 11 models, the averaged Δ SSAT at the 21 proxy locations and the pan-Arctic average Δ SSAT are inversely correlated with Δ SIA ( r = - 0.86 <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="49pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="9657313141bbfae45c345d44f0c9138f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-19-883-2023-ie00001.svg" width="49pt" height="10pt" src="cp-19-883-2023-ie00001.png"/></svg:svg> and −0.79 , respectively). In other words, the models show that a larger Arctic warming is associated with a greater sea ice reduction. Using the proxy-record-averaged Δ SSAT of 4.5±1.7 K and the relationship between Δ SSAT and Δ SIA suggests an estimated sea ice reduction of 4.2 ± 1.4 × 10 6 <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="72pt" ...